Silibinin ameliorates LPS-induced memory deficits in experimental animals - Joshi R.; Garabadu D.; Teja G.R.; Krishnamurthy S. (My University, 2025)
Neuroinflammation is considered as one of the predisposing factor in the etiology of several neurodegenerative disorders. Therefore, the objective of the present study was to evaluate the protective effect of silibinin (SIL) in the lipopolysaccharide (LPS)-induced neuroinflammatory model. The effect of SIL on memory function was also evaluated on normal rats without LPS administration. In the first experiment, male rats were divided into five groups. Except control group animals, all rats received bilateral intracerebroventricular injection of LPS (5. μg/5. μl) into lateral ventricles on the first day of the experimental schedule. Control rats received bilateral intracerebroventricular injection of artificial cerebrospinal fluid into lateral ventricles. SIL in doses of 50, 100 and 200. mg/kg, p.o. was administered 1. h before LPS injection and continued for 7. days. On Day-7, SIL attenuated the LPS-induced long-term and working memory loss in elevated plus and Y-maze test respectively. Further, SIL dose-dependently attenuated LPS-induced decrease in acetylcholine level and increase in the acetylcholinestrase activity in hippocampus and pre-frontal cortex. SIL ameliorated LPS-induced decrease in the mitochondrial complex activity (I, IV and V) and integrity, increase in lipid peroxidation and decrease in the activity of superoxide dismutase in both the brain regions. SIL attenuated amyloidogenesis in the hippocampus, while it decreased the LPS-induced increase in the level of NFκB in the pre-frontal cortex. In another study, SIL dose-dependently, enhanced memory functions in the normal rats, indicating its nootropic activity. Hence, SIL could be a potential candidate in the management of neuroinflammation-related memory disorders. © 2014 Elsevier Inc.